Logico- Semantic Relations in Bataknese Traditional Wedding Ceremony - Feriyanti Elina Gultom (Britain International for Academic Research (BIAR-Publisher), 2020)
This article explores the logico-semantic relation in communication in Bataknese traditional wedding ceremony. The dominant relation to communicate meanings as such offspring, prosperity, dignity, health, and long life of the wed are in the context of register, culture, text purpose, and ideology of Bataknese in delivering a wedding speech. Logico-semantic relation system and contextual components function as a network system to communicate sociocultural meanings in a wedding speech. This study was also aimed to identify the types of logical relations and the use of logical relations in Bataknese traditional wedding ceremony. This study was conducted by applying descriptive qualitative method. The source of data was taken from the utterancess of Parhata in Bataknese traditional wedding ceremony. The technique for analyzing the data was descriptive qualitative research based on Hancock. The result of this research was types of logical relations found in Bataknese traditional wedding ceremony, namely paratactic enhancement (33.75%), hypotactic enhancement (28.75%), paratactic extension (15 %), paratactic elaboration (12.5%), hypotactic elaboration (6.25 %), hypotactic extention (2.5%), and paratactic locution (1.25%). And the realized of logico-semantic relations in Raja Parhata’s utterances mostly appears by using conjunction jadi (so), molo (if) and holani (that all), adverbial clause dungi (after that), verb baen (play) and preposition tu (to).